Edukasi dan Pemberdayaan Kelompok Tani melalui Pembuatan Produk Biostimulan Tanaman: Education and Empowerment of Farmer Groups through Making Products of Plant Biostimulant - Sukma Agustin Dyan Tika; Anjar Maharani; Ike Ratna Setyo Pratiwi; Muhammad Nasrul Haq; Anggriawan, Rendy (Program Studi Ilmu Tanah, Fakultas Pertanian, Universitas Jember, 2023)
The current condition of agricultural land has broadly declined in soil quality and health caused by the excessive use of synthetic materials without paying attention to future agriculture sustainability. Soil as a planting medium plays an essential role in cultivated plants' growth and as a nutrient provider. Apart from using organic fertilizer, materials that can be used to support plant production are biostimulants. Plant biostimulants are substances or microorganisms applied to plants rather than as fertilizer to increase the efficiency of nutrient absorption abiotic stress tolerance, and improving plant characteristics/quality. This community service activity aims to educate the Gumukmas farmer group on manufacturing plant biostimulant products. The results show that the farmer group has understood a series of processes for making and utilizing biostimulants, as demonstrated by the product results from the Gumukmas farmer group. Farmer groups need regular assistance in online marketing strategies for biostimulant products so that the products can be more widely known and sales will increase.